Praktik Denda Keterlambatan Pelunasan Produk Pembiayaan Arrum Haji di Pegadaian Syariah Blauran Surabaya dalam Tinjauan Hukum Islam - Suad Qurrotul Aini (Maliyah : Jurnal Hukum Bisnis Islam, 2020)
This study aims to answer questions about the mechanism for determining penalties for late payment of Arrum Haji financing products at the Blauran Surabaya branch of Sharia Pawnshops and analysis of Islamic law both in fiqh and fatwa DSN MUI no. 43 of 2004. Sharia pawnshops are inseparable from the risk of loss, so that compensation (ta’wid) is enforced. In its implementation, Sharia Pawnshops include the amount of compensation in the contract agreement, while it is stated in the special provisions of Fatwa DSN MUI No. 43 of 2004 concerning Compensation (ta'wid) stating that the amount of compensation may not be included in the contract agreement. The results of this study indicate that the determination of the amount of compensation (ta'wid) is not fully in accordance with the legal requirements of ta'wid if the losses incurred are not due to real losses and only in the form of losses that are only estimated, as well as regarding penalties for late repayment of financing. or what is known as ta'wid (compensation) according to the fatwa DSN-MUI No. 43 of 2004, this practice is not appropriate because the fatwa is not allowed to state the amount of compensation/fines for losses or damages. customer negligence, but in practice Sharia Pawnshops include the amount of compensation in the contract.